Post-operative pain behaviour associated with surgical castration in donkeys (Equus asinus) - de Oliveira, Maria Gláucia Carlos; Luna, Stelio P. L. [UNESP]; Nunes, Talyta Lins; Firmino, Paulo R.; de Lima, Amara Gyane A.; Ferreira, Josiel; Trindade, Pedro H. E. [UNESP]; Júnior, Raimundo A. B.; de Paula, Valéria Veras (Wiley, 2020)
Background: Recognising pain in donkeys is challenging because they are stoic. Objectives: To identify the responses of donkeys before and after surgical pain. Study design: Prospective, short-term longitudinal pre- and post-intervention observations. Methods: Forty adult donkeys underwent surgical castration after sedation with intravenous (IV) xylazine, induction with guaiphenesin/thiopental IV and maintenance of anaesthesia with isoflurane and local anaesthetic blockade. Four hours after recovery from anaesthesia, flunixin meglumine 1.1 mg/kg, dipyrone 10 mg/kg and morphine 0.2 mg/kg IV were administered. Behavioural responses exhibited by the animals housed in individual stalls were recorded in four 30-min videos: before castration (M0), and 3.5-4.0 hours (M1), 5.5-6.0 hours (M2) and 23.5-24.0 hours after recovery from anaesthesia (M3). To exclude the influence of insects, the behaviour of six apparently pain-free donkeys was compared with and without the presence of faeces and urine in the stall. Results: When compared with presurgical baseline behaviours (M0), after surgery (M1) donkeys raised their pelvic limbs more (P =.003). When compared with M1, after analgesia (M2), the median frequencies of ear movements (44 vs 16; P <.001), head shaking (7 vs 1; P <.001), head turning (5 vs 0; P <.001) and lifting of the both limbs (7 vs 0; P =.008) decreased; feeding (0 vs 29; P <.001) and water intake (0 vs 0, range 0-1 vs 0-7; P =.05) increased. The dirty stall increased tail (53 vs 80; P =.03), head (16 vs 30; P =.03) and ear movements (50 vs 78; P =.04). Main limitations: The dirty stall and presence of insects possibly contributed to the expression of behaviours unrelated to pain. Conclusion: Lifting the pelvic limbs was the only specific pain behaviour after castration in donkeys. Analgesia restored appetite and water intake and reduced the frequency of head shaking and turning, ear movement and lifting the limbs. Tail, head and ear movements are unspecific responses related both to pain and a dirty stall, and are confounding factors when pain is assessed in donkeys in the presence of insects.
Keywords: analgesia; castration; donkeys; horse; well-being